2004
DOI: 10.1111/j.1365-2249.2004.02640.x
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte derived dendritic cell responses in common variable immunodeficiency

Abstract: SUMMARYThe phenotype and function of monocyte derived dendritic cells (MdDC) were investigated in 25 patients with common variable immunodeficiency (CVID) to test for abnormalities that might help explain the failure of antibody production. Using MHC class II DR and CD86 as markers of maturation, DCs from the majority of CVID patients were normal. However 5 patients, the majority of whom had affected family members who had previously been shown to have a susceptibility genetic locus in the MHC region, expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 25 publications
2
26
0
1
Order By: Relevance
“…These results are consistent with the fi ndings of Bayry et al that showed a severely perturbed differentiation and maturation of DCs in CVID patients with decreased expression of CD40, CD80, HLA-DR and other co stimulatory molecules, that resulted in impaired T cell activation and proliferation [17]. Defective antigen presentation of CVID patient's DCs has been also shown by others [32,33]. Scott-Taylor et al, demonstrated a fundamental defect in the maturation of CVID patients MDCs and reduction in HLA-DR expression after LPS stimulation leading to defective antigen presentation and subsequent antibody production [32].…”
Section: Discussionsupporting
confidence: 81%
“…These results are consistent with the fi ndings of Bayry et al that showed a severely perturbed differentiation and maturation of DCs in CVID patients with decreased expression of CD40, CD80, HLA-DR and other co stimulatory molecules, that resulted in impaired T cell activation and proliferation [17]. Defective antigen presentation of CVID patient's DCs has been also shown by others [32,33]. Scott-Taylor et al, demonstrated a fundamental defect in the maturation of CVID patients MDCs and reduction in HLA-DR expression after LPS stimulation leading to defective antigen presentation and subsequent antibody production [32].…”
Section: Discussionsupporting
confidence: 81%
“…3 Thus, the IL-7 dysfunction may also be involved in the defective dendritic cell function recently described in CVID. 19,20 Considering the role of IL-7 in both development and peripheral homeostasis of lymphocytes, 3 it is conceivable that the abnormal IL-7 function as demonstrated in this study may be involved in the skewing of lymphocyte subsets and in the development of an impaired T-and B-cell function in some CVID patients. For personal use only.…”
Section: Resultsmentioning
confidence: 84%
“…The number and function of T cells in XLA patients are generally normal. We showed that DC from CVID patients exhibit defective differentiation [26,27]. However, DC that differentiated in the presence of IVIg presented with an upregulated expression of CD1a and the costimulatory molecules CD80, CD86 and CD40, compared to DC in the presence of autologous plasma alone [28].…”
Section: Ivig Exerts An Agonistic Effect On DC Differentiation At Phymentioning
confidence: 94%